Social qualities of time and space created in performing arts of West Java The implications for safeguarding living culture - Wim van Zanten (Wacana: Journal of the Humanities of Indonesia, 2012)
Collective representations of "time" do not passively reflect time, but time and space are mediated by society. By our social practices, such as making music and dancing, we create time. Different cultural groups may experience and perceive time in different ways, and also within one cultural group the quality of time is not always experienced in the same way. Anthropological studies have shown that in each cultural group different perceptions of time co-exist. For instance, time generally tends to be perceived as both a linear flow and as repetitive. We should not confuse metaphysical and sociological arguments about time: time in music and other performing arts operates at the social and not at the metaphysical level. The essay discusses a variety of social qualities of time and space as it becomes manifest in some performing arts of West Java and the implications for their safeguarding.